Evaluation of nematodes and artificial artemia as feed for pacific white shrimp in a biofloc nursery system - Sommer, Nils Phillip (2019)
The global aquaculture production is growing immensely in all aspects and has already surpassed the output from wild caught fish and shellfish industries. The farming of Penaeus vannamei is one of the biggest contributors to this market. But many early stages of aquaculture depend on the finite and volatile resource Artemia as a live feed. This dependency has been identified as a bottleneck for future growth and sustainability progress. In this experiment, one artificial Artemia product and one nematode species were tested and evaluated in a feeding trial as potential replacements for live Artemia in a zero-water exchange biofloc nursery system. P. vannamei post larvae (PL) were stocked at a density of 60 PL/L in 60-L tanks. They were reared from PL12 – PL33 and fed 8 times per day with a dry feed (DF). Different treatments with four replicates each received a diet supplement of either live nematodes (N), live Artemia (LA), artificial Artemia (AA), or DF (control, C). The PL that received the live diets had nearly twice the survival rate compared to the ones only fed inert diets (N: 94 ± 6%, LA: 91 ± 7%, AA: 53 ± 11%, C: 51 ± 10%). Growth parameters were slightly better in the two inert diet groups (wet weight: N: 22.5 ± 5 mg, LA: 22.5 ± 5 mg, AA: 35 ± 5.7, C: 35 ± 10; Total length: N: 15.8 ± 3.9 mm, LA: 15.8 ± 3.2, AA: 17.1 ± 5.1 mm, C: 17.3 ± 5.0). No significant differences were detected in survival to salinity stress. In addition, beneficial effects on the biofloc and on the water quality were observed in the live diet groups and their causation should be further investigated. The results show that the nematode species Panagrolaimus sp. (NFS 24-5) can completely replace live Artemia in a co-feeding regime.